Disturbance chemical cues determine changes in spatial occupation by the convict cichlid Archocentrus nigrofasciatus - Jordao, L. C. (Elsevier B.V., 2004)
I studied the effect of disturbance chemical cues on fish that make trade-offs between foraging in an open area and remaining in a safe refuge. I used convict cichlids Archocentrus nigrofasciatus that were either visually exposed to a predator (n = 8) or exposed to water conditioned by chemical cues from disturbed conspecifics (n = 8). Fish visually exposed to a predator decreased their ingestion rate and spent more time in the refuge than in the foraging area, while fish receiving water from frightened conspecifics did not alter their ingestion rate or time spent in the refuge and foraging site, but increased their spatial occupation (i.e., motion). These results suggest that convict cichlids recognized the predator by visual cues. Moreover, disturbance cues are a form of threatening public information that may increase fish spatial occupation due to increased exploring behaviour; but is not sufficiently alarming to alter feeding or increase refuge use. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: chemical communication; decision-making; disturbance cues; fish; public information